Physicochemical and sensory properties of coconut milk-based functional ice cream formulated with inulin, protein isolate, and pineapple - Arie Nugroho; Sefanadia Putri; Reni Indriyani; Asep Rusyana (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
The demand for dairy-free frozen desserts is increasing; however, non-dairy matrices often have weak structures, limited water retention, and sensory defects. This study aimed to optimize a dairy-free ice cream formulated with coconut milk, date syrup, inulin, pea protein isolate, pineapple, and egg yolk, and evaluate its physical, nutritional, and sensory characteristics. Methods: A completely randomized design was used from March to May 2026. Six formulations (control and P1–P5) were tested at Poltekkes Tanjungkarang and Politeknik Negeri Lampung. Physical properties, including water-holding capacity and first dripping time, were assessed based on the proximate composition and sensory acceptability using a 9-point hedonic scale. Data were analyzed using one-way analysis of variance, followed by Duncan’s test. The results showed that formulation modifications significantly affected all evaluated profiles (p < 0.001). P3 was identified as optimal, with 22.81% protein, 26.52% fat, 13.84% fiber, 43.48% total solids, 47.36% water-holding capacity, and a first dripping time of 240.33 s. P3 also had the highest aroma (6.14), taste (6.51), and mouthfeel (6.19) scores among all the samples. In conclusion, P3 exhibited the most favorable nutritional, physical, and sensory profiles among the tested formulations. This formulation may support the development of nutrient-dense dairy-free frozen desserts, although product classification should be clarified because egg yolk was included.